Präexistente Musik im Film - Rudolph, Pascal (2022)
From the end of the world with Richard Wagner's "Tristan and Isolde" to the vocal performance of a Björk sentenced to death on the gallows to Johann Sebastian Bach's organ music as an explanatory model for hypersexuality: as strange as Lars von Trier's cinema may seem, it offers a wide range of opportunities to reflect on a musical phenomenon that shapes a large part of today's art and entertainment world. Lars von Trier's films mainly feature music that existed before the films. On the one hand, such pre-existing music has a distinct life of its own; on the other, something new emerges from the cinematic appropriation. Using the example of one of the most influential directors of our time, Pascal Rudolph examines how filmmakers adapt music and how this creates meanings and effects. Based on unpublished production material and insider interviews, this book is the first to offer detailed insights into the work on Lars von Trier's film projects in particular, but also into the working processes of film music design in general. The study does justice to the musical diversity in the films through its multi-perspective and transdisciplinary approach. In this way, the ten chapters shed light on the interaction between music and film from different angles. Awarded the 2022 Doctoral Prize of the Gesellschaft für Musikforschung.